Pengaruh Perputaran Piutang Dan Modal Kerja Terhadap Profitabilitis pada UKM. Keripik Sehi Sukabumi - muthi, Farida rianti (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
This study aims to determine the effect of the accounts receivable turnover and working capital on profitability in SMBs. Sehi Sukabumi in 2009-2013. Variable used is the accounts receivable turnover, working capital and profitability. The secondary data used in this study are the financial statements of SMBs. The analytical method used is multiple linear regression, an efficient test of determination, the classical assumption and to test the hypothesis used test-f and t-test. The results of the analysis of this study is the accounts receivable turnover and working capital has no effect on the level of profitability simultaneously. While partial analysis showed no effect on the accounts receivable turnover and profitability levels of working capital effect on the level of profitability.